Apprendre à écrire en vue de contextes professionnels : recherche anglophone Nord Américaine à partir de perspectives socio-culturelles - David R. Russell (Éducation et Socialisation)
The goal of this article is to outline how the teaching of university writing in North America (US and Canada) has profited from sociocultural research on the relation between professional writing and writing in the academic disciplines. North America has a tradition of research on writing in professional contexts, based on the theory of genre as social action. The results of this research show the complex relations between professional writing and the writing of university students, at different levels. The social-psychological positions of the students and the teachers are both defined by—and put in tension by—the genres and the practices of professionals, even if the students and teachers are not conscious of this influence. And certain pedagogical interventions have been developed for certain university programs of study based on this research.